In a closet hidden : the life and work of Mary E. Wilkins Freeman - Glasser, Leah Blatt, 1951- (University of Massachusetts Press, 1996)
"The first literary biography of a much-neglected American writer, this book explores the multiple tensions at the core of Mary E. Wilkins Freeman's life and work. A prolific short story writer and novelist, Freeman (1852-1930) developed a reputation as a local colorist who depicted the peculiarities of her native New England. Yet as Leah Blatt Glasser shows, Freeman was one of the first American authors to write extensively about the relationships women form outside of marriage and motherhood, the role of work in women's lives, the complexity of women's sexuality, and the interior lives of women who rebel rather than conform to patriarchal strictures." "In a Closet Hidden traces Freeman's evolution as a writer, showing how her own inner conflicts repeatedly found expression in her art. As Glasser demonstrates, Freeman's work examined the competing claims of creativity and convention, self-fulfillment and self-sacrifice, spinsterhood and marriage, lesbianism and heterosexuality."--Jacket.